Children, adults, best interests and rights. (March 2013) - Archard, David
This article seeks, first, to disarm some of the principal criticisms of the best interests principle as having an indeterminate content. It then considers how a best interests principle stands in relation to other principles, in particular according to the child a 'voice' on matters affecting its interests. It seeks to show that there is an important distinction between a 'threshold' and 'weighting' view of a child's capacities, which has significant implications for how we think from a rights perspective both about the child and about the adult. The article contrasts its own approach from that of John Eekelaar's 'dynamic self-determinism', and concludes by suggesting ways in which the case of children can illuminate the broader understanding of adult rights to autonomy and of liberal anti-paternalism.